ZnxFe3- xO4 (0 ≤ x ≤ 1.0) Magnetic Nanoparticles Functionalized with Polyacrylic Acid (PAA) - Kamzin, A. S.; Caliskan, G.; Dogan, N.; Bingolbali, A.; Semenov, V. G.; Buryanenko, I. V. (PLEIADES PUBLISHING LTD, 2023)
Studies of the properties of ZnxFe3 - O-x(4) (x = 0, 0.25, 0.5, 0.75, 1.0) magnetic nanoparticles synthesized by a modified hydrothermal method are presented in comparison with the properties of the same nanoparticles stabilized with polyacrylic acid ZnxFe3 - O-x(4)@PAA. The structure, size, morphology, and magnetic properties of the samples were studied by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT IR), physical properties measurements (PPMS), and M & ouml;ssbauer spectroscopy. The synthesized nanoparticles are single-phase, without additional impurities, have a narrow size distribution and are in the superparamagnetic phase. From the (XRD) measurements, it was found that with an increase in the Zn content from x = 0 to x = 1.0, the sizes of the nanoparticles were increasing from 17 to 33 nm. Analysis of the M & ouml;ssbauer spectroscopy data showed that when doped with Zn ions from x = 0 to x =1.0, the sizes of the nanoparticles were decreasing from 15 to 5 nm. The results of the M & ouml;ssbauer studies showed that both ZnxFe3 - O-x(4) and ZnxFe3 - O-x(4)@PAA has a core/shell type structure in which the core is magnetically ordered, whereas the shell does not have magnetic ordering. M & ouml;ssbauer studies indicate that the coating of citric acid particles leads to their isolation from each other, reducing or eliminating interactions between particles, reducing the thickness of the paramagnetic shell, and thereby increasing the diameter of the core, which is in a magnetically ordered state.
Keywords: ferrite-spinel nanoparticles; hydrothermal synthesis; polyacrylic acid functionalization; Mossbauer spectroscopy; properties; crystal and magnetic structure; IRON-OXIDE NANOPARTICLES; FE3O4 NANOPARTICLES; ABSORPTION RATE; MOSSBAUER; HYPERTHERMIA; NANOCRYSTALS; DEPENDENCE; SIZE; Physics